Impact of Financial and Non-financial Benefit on Employees’ Job Satisfaction (Journal of Management, 2020)
This study examines the impact of financial benefit, training, reward, and career development opportunity on employees’ job satisfaction. This study is based on Likert scale data. There are forty questions included in the questionnaires excluding demographic variables. Each attribute contains eight questions. The primary data are obtained through the survey method. These collected data are analyzed by using descriptive statistics, Pearson correlation coefficient, and ordinary least squares regression model. The Statistics Package for Social Sciences (SPSS) is used for the analysis of data. The results indicate that the independent variables (financial benefit, training, reward, and career development opportunity) positively impact on job satisfaction.